JENIS-JENIS IKAN YANG TERTANGKAP DI BATANG SANGIR NAGARI LUBUK MALAKO SOLOK SELATAN (Universitas PGRI Sumatera Barat, 2022)
The diversity of fish species in the Sangir River is still quite large, but there is no scientific data so that the types of fish caught in the Sangir River have not been accurately recorded. This study aims to identification the fish caught in the Sangir River Lubuk Malako. The method used in this study was a descriptive survey with a total sampling technique by assigning 3 stations with different water conditions. Sampling started from 25 June to 12 July 2022. The samples were identified in the Zoology Laboratories PGRI Sumatera Barat University. The results showed that there were 19 species of fish consisting of 19 genera, 10 families, 5 orders caught in the Sangir River.